2018
DOI: 10.1093/nar/gky272
|View full text |Cite
|
Sign up to set email alerts
|

Multiple RPAs make WRN syndrome protein a superhelicase

Abstract: RPA is known to stimulate the helicase activity of Werner syndrome protein (WRN), but the exact stimulation mechanism is not understood. We use single-molecule FRET and magnetic tweezers to investigate the helicase activity of WRN and its stimulation by RPA. We show that WRN alone is a weak helicase which repetitively unwind just a few tens of base pairs, but that binding of multiple RPAs to the enzyme converts WRN into a superhelicase that unidirectionally unwinds double-stranded DNA more than 1 kb. Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 47 publications
8
47
0
Order By: Relevance
“…Alternatively, more than one protein unit could bind to form an active unwinding complex. The observed behavior was similar to that seen for BLM (Wang et al , ), WRN (Lee et al , ), and the likely BLM homolog from Arabidopsis thaliana , AtRecQ2 (Klaue et al , ). For AtRecQ2, the transition between unwinding and rezipping most likely involves strand switching (Klaue et al , ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Alternatively, more than one protein unit could bind to form an active unwinding complex. The observed behavior was similar to that seen for BLM (Wang et al , ), WRN (Lee et al , ), and the likely BLM homolog from Arabidopsis thaliana , AtRecQ2 (Klaue et al , ). For AtRecQ2, the transition between unwinding and rezipping most likely involves strand switching (Klaue et al , ).…”
Section: Resultssupporting
confidence: 77%
“…DNA unwinding by Sgs1 was found to be highly dynamic, involving many repetitive unwinding events separated by either rapid DNA rezipping or slower DNA rewinding. Sgs1 shares this highly dynamic activity pattern with other RecQ family helicases from prokaryotes (Harami et al , ; Bagchi et al , ) and eukaryotes (Klaue et al , ; Wang et al , ; Lee et al , ). It is thought that the switching between unwinding and rewinding involves repeated strand switching events to allow direction reversals of the helicase (Klaue et al , ).…”
Section: Discussionmentioning
confidence: 92%
“…This indicated that a burst was likely initiated by the binding of a single Sgs1 unit (a molecule or a complex), which subsequently originated all events of the burst until the protein finally dissociated. Such behavior is similar to that observed for BLM [29], WRN [30] and the likely BLM-homologue from Arabidopsis thaliana, AtRecQ2 [31]. For the latter it has been shown that the transition between unwinding and rezipping most likely involves strand switching that brings the enzyme in a more loosely bound state since it lacks the DNA junction in its wake [31].…”
Section: Resultssupporting
confidence: 73%
“…DNA unwinding by Sgs1 was found to be highly dynamic, involving many repetitive unwinding events separated by either rapid DNA rezipping or slower DNA rewinding. Sgs1 shares this highly dynamic activity pattern with other RecQ family helicases from prokaryotes [45,46] and eukaryotes [29][30][31]. It is thought that the switching between unwinding and rewinding involves repeated strand switching events to allow direction reversals of the helicase [31].…”
Section: Discussionmentioning
confidence: 99%
“…In homologous recombination WRN interacts with RAD52 and increases its strand annealing activity, whist also modulating WRN helicase activity in a structure dependent manner (13). WRN has been shown to interact via acidic repeats between the helicase and nuclease regions with Replication Protein A (RPA) and this interaction is was found to stimulate WRN helicase activity (14)(15)(16). In telomere metabolism WRN has been found to interact with the shelterin complex components TRF2 and POT1, and this interaction stimulates WRN helicase activity (17,18).…”
Section: Introductionmentioning
confidence: 99%